ANALISIS BAHAN PENGAWET BENZOAT PADA SAOS TOMAT YANG BEREDAR DI WILAYAH KOTA DENPASAR - I M. Siaka (Jurnal Kimia (Journal of Chemistry), 2009)
This paper reports the determination of benzoate, as preservative, in tomato sauces distributed in Denpasar.The analysis was performed by the technique of acid-base titration following solvent extraction of the benzoate withdiethylether. Qualitatively, it was found that the sauce samples both branded and unbranded ones contained benzoate.Quantitatively, it was obtained that the benzoate content in the tomato sauces varied in a range of 600.12 – 1271.86mg/kg. Generally, all branded tomato sauces contained benzoate less than that of maximum limit allowed by theregulation of Health Ministry of RI No. 722/MENKES/Per/IX/1988 (1000 mg/kg). On the other hands, about 33% ofthe unbranded sauce samples contained benzoate more than the maximum limit allowed by the regulation.